PARENTAL BONDING DENGAN PERILAKU SEKSUAL PADA REMAJA - Mardhiah Mardhiah; Lilis Pujiati; Icceng Sidabutar; Verany Melinda Purba; Nazira Addini Batubara; Hotnida Br Sitorus (Indonesian Trust Health Journal, 2026)
Parental bonding plays a crucial role in shaping adolescent behavior, including the regulation of sexual behavior. The emotional connection established between parents and adolescentscharacterized by attention, affection, and balanced supervision can serve as a protective factor against risky sexual behavior. Conversely, suboptimal parental bonding can increase adolescents' vulnerability to environmental influences and urges to engage in sexual behaviors that deviate from social norms. This study aimed to examine the relationship between parental bonding and adolescent sexual behavior at SMA Panca Budi Medan. This study employed a quantitative research method with a descriptive-correlational design and a cross-sectional approach. The study population consisted of 675 students; sample size determination using G*Power with an effect size of 0.3, an alpha error probability of 0.05, and a power of 0.85 resulted in a sample of 75 respondents. Research instruments included questionnaires assessing parental bonding and adolescent sexual behavior. Spearman’s rho correlation was used for statistical analysis. Bivariate analysis results indicated a significant relationship between parental bonding and adolescent sexual behavior, with a p-value of 0.006 (<0.05) and a correlation coefficient of r = -0.317. The relationship was negative, indicating that better parental bonding is associated with lower levels of risky sexual behavior among adolescents. Thus, it can be concluded that there is a significant relationship between parental bonding and adolescent sexual behavior at SMA Panca Budi Medan. The findings of this study are expected to serve as a basis for parents, schools, and healthcare professionals to enhance the family's role—through attention, communication, and balanced supervision as a means of preventing risky sexual behavior among adolescents. Abstrak Parental Bonding memiliki peran penting dalam membentuk perilaku remaja, termasuk dalam pengendalian perilaku seksual. Hubungan emosional yang terjalin antara orang tua dan remaja melalui perhatian, kasih sayang, serta pengawasan yang seimbang dapat menjadi faktor protektif terhadap perilaku seksual berisiko. Sebaliknya, Parental Bonding yang kurang optimal dapat meningkatkan kerentanan remaja terhadap pengaruh lingkungan dan dorongan perilaku seksual yang tidak sesuai norma. Tujuan penelitian ini adalah untuk mengetahui hubungan Parental Bonding dengan perilaku seksual remaja di SMA Panca Budi Medan. Penelitian ini menggunakan metode penelitian kuantitatif dengan desain deskriptif korelasi melalui pendekatan cross sectional. Populasi dalam penelitian ini berjumlah 675 siswa dengan penentuan sampel menggunakan G Power dengan effect size sebesar 0,3, alpha error probability sebesar 0,05 dan power sebesar 0,85 sehingga diperoleh sampel sebanyak 75 responden. Instrumen penelitian berupa kuesioner Parental Bonding dan perilaku seksual remaja. Uji statistik yang digunakan adalah uji korelasi Spearman’s rho. Hasil analisis bivariat menunjukkan adanya hubungan yang signifikan antara Parental Bonding dengan perilaku seksual remaja, dengan nilai p-value sebesar 0,006 (<0,05) dan koefisien korelasi r = -0,317. Arah hubungan bersifat negatif, yang menunjukkan bahwa semakin baik Parental Bonding orang tua, maka semakin rendah perilaku seksual berisiko pada remaja. Dengan demikian, dapat disimpulkan bahwa terdapat hubungan yang signifikan antara Parental Bonding dengan perilaku seksual remaja di SMA Panca Budi Medan. Hasil penelitian ini diharapkan dapat menjadi dasar bagi orang tua, sekolah, dan tenaga kesehatan dalam meningkatkan peran keluarga melalui perhatian, komunikasi, dan pengawasan yang seimbang sebagai upaya pencegahan perilaku seksual berisiko pada remaja.